2008
DOI: 10.1158/0008-5472.can-08-1171
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylator Phenotype in Sporadic Colon Cancer: Study on a Population-Based Series of 582 Cases

Abstract: The CpG island methylator phenotype (CIMP) is a distinct phenotype in colorectal cancer, associated with specific clinical, pathologic, and molecular features. However, most of the studies stratified methylation according to two subgroups (CIMP-High versus No-CIMP/CIMP-Low). In our study, we defined three different subgroups of methylation (No-CIMP, CIMP-Low, and CIMP-High) and evaluated the prognostic significance of methylation status on a populationbased series of sporadic colon cancers. A total of 582 colo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
209
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(233 citation statements)
references
References 19 publications
22
209
0
2
Order By: Relevance
“…[26][27][28] Along the adenoma-carcinoma sequence, colorectal tumorigenesis can progress through either chromosomal instability pathway with multiple alterations in chromosome number, chromosomal rearrangements, or gene amplications or the microsatellite instability pathway as a result of a germiline mutation in a DNA mismatch repair protein. 29 More recently, colorectal carcinomas that exhibit high levels of promoter methylation of CpG islands have been identified (CIMP-high, CIMP-H), 30,31 and these CIMP-H carcinomas are thought to arise through a precursor sessile serrated polyp/adenoma. 29 Abnormalities of the Wnt signaling pathway, particularly APC inactivation with nuclear localization of b-catenin, and activating KRAS mutations are common events in the adenoma-carcinoma sequence of the chromosomal instability pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Along the adenoma-carcinoma sequence, colorectal tumorigenesis can progress through either chromosomal instability pathway with multiple alterations in chromosome number, chromosomal rearrangements, or gene amplications or the microsatellite instability pathway as a result of a germiline mutation in a DNA mismatch repair protein. 29 More recently, colorectal carcinomas that exhibit high levels of promoter methylation of CpG islands have been identified (CIMP-high, CIMP-H), 30,31 and these CIMP-H carcinomas are thought to arise through a precursor sessile serrated polyp/adenoma. 29 Abnormalities of the Wnt signaling pathway, particularly APC inactivation with nuclear localization of b-catenin, and activating KRAS mutations are common events in the adenoma-carcinoma sequence of the chromosomal instability pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its predictive role, KRAS mutation has not been shown as a prognostic marker in many large-scale studies (Finkelstein et al, 1993;Samowitz et al, 2000;Gnanasampanthan et al, 2001;Ince et al, 2005;Barault et al, 2008b;Zlobec et al, 2009;Ogino et al, 2009a;Ogino et al, 2009b;Roth et al, 2010), except for one large study (Barault et al, 2008a). Overall evidence supports a null prognostic role of KRAS mutation even if a previous meta-analyses (Andreyev et al, 1998;Andreyev et al, 2001) led to wrong conclusions likely due to the well-known positive publication bias.…”
Section: Kras Somatic Mutationsmentioning
confidence: 98%
“…Along with others, we have reported a worse prognosis in colorectal cancer patients with CIMP-low or CIMP-high, compared with CIMPnegative tumors, particularly in combination with MSS. 4,[9][10][11][12] However, results from other large studies have not been entirely consistent, [13][14][15][16][17][18] and consensus has thus not been reached. One factor contributing to the discrepancy of results in the many studies is the lack of information regarding BRAF mutation, which has shown to be a major confounding factor in studies of CIMP status and colorectal cancer patient survival.…”
mentioning
confidence: 96%